2018
DOI: 10.1186/s40248-018-0149-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe acute exacerbations of COPD: an updated narrative review

Abstract: BackgroundPatients with chronic obstructive pulmonary disease (COPD) may experience an acute worsening of respiratory symptoms that results in additional therapy; this event is defined as a COPD exacerbation (AECOPD). Hospitalization for AECOPD is accompanied by a rapid decline in health status with a high risk of mortality or other negative outcomes such as need for endotracheal intubation or intensive care unit (ICU) admission. Treatments for AECOPD aim to minimize the negative impact of the current exacerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 159 publications
0
59
1
Order By: Relevance
“…Interestingly, polymorphisms in the vitamin D binding protein gene might also be related to higher exacerbation frequencies (Ishii 2014), suggesting a relationship between vitamin D and the occurrence of exacerbations. Current strategy to treat exacerbations in COPD includes long-acting bronchodilators and longterm use of inhaled corticosteroids or macrolide antibiotics but they are all modestly effective and evidence on the preferred drug and optimal treatment duration are lacking [82]. An attractive alternative target for intervention studies in COPD is the vitamin D pathway.…”
Section: Vitamin D In Copd and Exacerbationsmentioning
confidence: 99%
“…Interestingly, polymorphisms in the vitamin D binding protein gene might also be related to higher exacerbation frequencies (Ishii 2014), suggesting a relationship between vitamin D and the occurrence of exacerbations. Current strategy to treat exacerbations in COPD includes long-acting bronchodilators and longterm use of inhaled corticosteroids or macrolide antibiotics but they are all modestly effective and evidence on the preferred drug and optimal treatment duration are lacking [82]. An attractive alternative target for intervention studies in COPD is the vitamin D pathway.…”
Section: Vitamin D In Copd and Exacerbationsmentioning
confidence: 99%
“…Acute exacerbation (AE) of COPD (AECOPD) is defined as episodes of acute worsening of respiratory symptoms (such as dyspnea, coughing, and sputum production) that require additional therapy [3,4]. Treatments for AECOPD aim to minimize the negative impacts of the current exacerbation and prevent subsequent events, such as relapse or readmission to the hospital [5]. AECOPD requiring hospitalization is associated with poor outcomes, including accelerated declines in muscle strength [6] and lung function [7], a reduced health status and quality of life (QOL) [8], accelerated disease progression [9], a significant risk of recurrent exacerbations, and an increased risk of mortality [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, treatment goals for patients with AECOPD are to minimize the negative impacts of these events and prevent their recurrence [13]. The management of severe AECOPD is divided into pharmacological (inhaled bronchodilators, steroids, and antibiotics) and nonpharmacological treatments (oxygen therapy, high-flow nasal therapy (HFNT), non-invasive mechanical ventilation (NIMV), and pulmonary rehabilitation (PR)) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The primary aim of AECOPD treatment was to minimize the clinical impact of the current exacerbation and to prevent subsequent deterioration events that may include readmission (Crisafulli, Barbeta, Ielpo, & Torres, ). Published AECOPD treatment guidelines exist (GOLD, ; NICE, ) although adherence has been found to be challenging (Lodewijck et al, ) with clinician‐reported barriers including poor familiarity with recommendations, low self‐efficacy and time constraints (Perez, Wisniveskya, Lurslurchachai, Kleinman, & Kronish, ).…”
Section: Introductionmentioning
confidence: 99%